Propostas para melhoria da integração entre desenvolvimento de produto e planejamento e controle da produção em ambiente ETO - Andrade, José Henrique de (2013)
The main objective of this thesis is to present proposals to improve the integration between Product Development (PD) and Production Planning and Control (PPC) in production systems that operate in Engineering-to-Order (ETO) environment. The specific objectives are: to develop a theoretical framework which identifies concepts and management tools applicable in business process studied that helps to explore integration opportunities; to map the studied scenario in order to understand it comprehensively in what it refers to interactions between PD and PPC; to identify the information technology tools used on studied companies, as well as ways to maximize their usage and to evaluate the proposals with the assistance of professionals who work at PD and PPC on the studied companies. The integration is critical for the production system operations performance, looking to reduce the time and costs for product placement in the market and to increase the quality of the products and services offered. To reach that goal, a literature review on the interest topics and case studies was performed to support the development of the proposals to improve the integration between PD and PPC. The case studies were carried out in large metal-mechanical companies that develop and manufacture capital goods on demand, located in the state of São Paulo. Among the proposals, models which attempt to describe, prescribe and represent aspects that can contribute to improving the integration between PD and PPC are presented, as well as a set of steps to be followed to achieve the process of improving the functional integration. It is expected that the results will contribute to a better understanding of the factors that enable a better integration between PD and PPC in this type of company as well as creating knowledge to the researched theories lines related to the topic and contribute to the management of the studied companies.